Analysing the Contemporary Essentials of Sustainable Gig Economy Workforce From the Lenses of Maqasid Shariah - Ishak, Amal Hayati; Mohamad, Siti Nor Amira; Ismail, Ahmad Thaqif; Abd Latib, Noor Aznaim; Sahari, Noorul Huda (Millah: Journal of Religious Studies, 2025)
Gig economy refers to the current trend of flexible work arrangements intermediated by present technological advances, benefitting both the gig workforce and businesses employing them, contributing to economic sustainability. Flexible work schedule enables the gig workforce to diverse work and earn additional income, while providing businesses a cost saving talent pool as their service is time-based or task based. Nevertheless, the flexibility challenges the gig workforce in terms of job security, employee rights and benefits, health and safety protection and income volatility. Therefore, employing a content analysis approach, this article deduces the contemporary essentials of the contract workforce in accordance with maqasid shariah, upholding the protection of five necessities: religion, life, intellect, dignity, and property. For that purpose, the challenges of the gig workforce are analysed and compared to the shariah's recommendations. The study concludes on insightful support as recommendations for the government to consider when developing and enhancing pertinent policies in safeguarding the welfare of the gig workers.